Is senior high school worth it? assessing the employability of senior high school graduates under the K to 12 basic education program - Gondra, Zarah Aline V.; Nepomuceno, Samantha Louise S.; Epetia, Ma. Christina F. (Quezon City School of Economics, University of the Philippines, 2019)
With the addition of two years in the K to 12 Basic Education Program, Senior High School (SHS) is seen as a path to better employment opportunities. The program is expected to produce more “globally competitive, employable and entrepreneurial” graduates as promised by the Department of Education. Furthermore, SHS graduates are also expected to be employed in at most “middle-skill jobs”. Our study aims to examine the current employability of SHS graduates, and the types of jobs acquired, using the data on the recent two batches of SHS graduates. We used probit and ordered probit for our regressions. Moreover, we also considered additional factors such as survey year, region, sex, age, area, and marriage that could affect the likelihood of employment of a graduate. Using Spence’s Signaling Theory (1973) our findings suggest that holding an SHS diploma is not an effective signal of employability and that it is the individual characteristics of the applicant that the employers pay more attention to when hiring. This implies that the program is not able to uphold its promise of better employment opportunities and “middle-skill” jobs for its first two batches of SHS graduates.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: K-12 (Education).